Psychological Study of the Stages of Grief in Postmodern Poems (Zien Journal of Social Sciences and Humanities, 2022)
This paper sheds the light on the psychological study of the five stages of the grief (Denial, Anger, Bargaining, Depression, Acceptance) in postmodern poems that are related to the theme of death and suicide. Ross model (1969) is adopted for the psychological analysis. Its analysis relies on the last three stages of grief(Bargaining, Depression, Acceptance) in postmodern poetry(poems). The paper analyzes the theme of death in the poems that are written by Allen Ginsberg and Anne Sexton, both of them have lost someone who is very close ( father, friend) and they wish to be dead before their death , they also want to die in the same way (suicide).